Is culture historically guilty? - Tortosa, Vigilio (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
Unlike a deliberale construction of History that thinkers such as Nietzsche or Freud woulddesignate as "guilty conscience", inserting the literary discomse in the dialectics of historyimplies dissipating the ghost of the "naturalization" which thas becn attempted lo forge the recentidyllic landscape of our Literatnre, Playwriters like Francisco Nieva have tried to lïght the ghost.so have writers of such different trends as Manuel Talens, Masoliver Ródenas, Sanchis Sinisterraor J.M Ullán, among others. The article ollers a selective review, within the frame of the so-called"democracy", that challenges that human feeling of cultural guilt. At the same time, it attemps toliberate Literature from all lhe historical restraints that have been in runetion over the years (genreclassifïcations, standards, generalions, etc, ) in order to challenge the non-critical aet of reading,so widely spread in our days.
Keywords: History; cultural guilt